The Synergistic and Attenuated Mechanism of Action of the Xihuang Pill in Dual Immunotherapy After Stenting for Advanced Cholangiocarcinoma: A Controlled Clinical Trial - Wang P; Wang YH; Tao Y; Zheng XL; Wang WC (International Journal of General Medicine)
Peng Wang,1,2 Yu-Huan Wang,2 Yun Tao,1 Xiang-Long Zheng,2 Wan-Chun Wang3 1Department of Interventional and Vascular Surgery, Affiliated Hospital of Jiangnan University, Wuxi, People’s Republic of China; 2Clinical Medical College, Jiangxi University of Chinese Medicine, Nanchang, People’s Republic of China; 3Department of Traditional Chinese Medicine Surgery, Affiliated Hospital of Jiangxi University of Chinese Medicine, Nanchang, People’s Republic of ChinaCorrespondence: Wan-Chun Wang, Department of Traditional Chinese Medicine Surgery, Affiliated Hospital of Jiangxi University of Chinese Medicine, 445 Bayi Avenue, Nanchang City, Jiangxi, 330006, People’s Republic of China, Email wwjx7469108@163.comPurpose: This study aims to investigate the synergistic and attenuation mechanism of Xihuang pill in the treatment of cholangiocarcinoma (CCA), thereby providing a reliable scientific basis for the selection of postoperative treatment strategies in cholangiocarcinoma patients.Methods: In total, 120 patients with advanced CCA who underwent stent implantation were divided into control group I (n = 40), control group II (n = 40), and observation group (n = 40). The patients in control group I were only treated with a tumor immunosuppressant (tislelizumab injection), the patients in control group II were administered tumor double immunotherapy (tislelizumab injection + thymalfasin injection), and the patients in the observation group were treated with Xihuang pill combined with tumor double immunotherapy. The therapeutic effect, side effects, coagulation function, tumor markers, and immune function were compared among the three groups.Results: Compared to the patients in control groups I and II, those in the observation group showed significantly longer activated partial thromboplastin time (APPT) and prothrombin time (PT), and lower fibrinogen (FIB) levels and platelet count (PLT) after treatment (P < 0.05). In the observation group, the levels of CD3+, CD4+, and CD4+/CD8+ increased, but the level of CD8+ decreased. The levels of CEA, CA125, CA19-9, CA242, and CA50 in serum decreased. The adverse reactions in the observation group were lower, while the objective remission rate (ORR) was significantly higher than their corresponding values in control groups I and II (42.5%vs17.5%, 27.5%) (P < 0.05). The 1-year overall survival rates of the control group I, control group II and observation group were 42.5%, 50% and 60%, and the difference was not statistically significant (P > 0.05).Conclusion: Xihuang Pill combined with dual immunotherapy can synergistically enhance anti-tumor efficacy and reduce treatment-related toxicity in patients with advanced CCA by regulating coagulation function and immune mechanisms.Keywords: cholangiocarcinoma, stent implantation, Xihuang pill, immunotherapy, enhanced efficacy and attenuated toxicity